Washed microbiota transplantation in an elderly patient with lymphocytic leukemia and Clostridioides difficile infection: A case report illustrating a triumph over complexity - Xinyu Zhang; Yuan Li; Bo Li; Jingwei Wu; Junmei Zhang; Xia Ding (Heliyon, 2024)
Background: Fecal microbiota transplantation (FMT) is recommended for treating patients with recurrent Clostridioides difficile infection (CDI). However, the therapeutic efficacy of FMT in elderly patients with complex medical conditions remains uncertain. The new method of FMT, washed microbiota transplantation (WMT) has been widely used in China to improve the safety of transplantation. Case report: A 94-year-old man with chronic lymphocytic leukemia (CLL) was admitted to our hospital due to recurrent diarrhea persisting for eight months. The patient had experienced multiple relapses of CDI despite receiving standard therapies. He underwent colonic transendoscopic enteral tubing (TET) and subsequently received WMT during the procedure. Following the treatment, no episodes of diarrhea or adverse events were observed, and the patient remained stable over a three-month follow-up period. Conclusion: This case demonstrates the efficacy and safety of WMT in treating elderly patients with CLL. The successful management of this case offers valuable clinical insights into the use of WMT for elderly CDI patients with complex medical conditions. Moreover, this report contributes practical experience regarding the administration of WMT through the colonic TET.